At a Court of General Sessions of the Peace, Oyer and Terminer, Assize and General Goal Delivery, holden at Charles-Town, in the province of South-Carolina, on the first day of October, 1741 : the chief justice's charge to the grand jury for the body of this province - Whitaker, Benjamin, -1751 (Printed by Peter Timothy, 1741)
1741 Chief Justice Benjamin Whitaker's charge to the grand jury along with a preface regarding their duties. The charge reviewed the various laws that could be violated, beginning with those of a religious nature, and continuing through all the various crimes.